Moisture Determination of Cocoa Beans by Microwave Oven - Ing, Stephen Tiong Mee (1990)
A statistical trial was conducted to compare microwave oven and air-heated oven methods for moisture determination of cocoa beans. The findings indicate that both methods are comparable in accuracy but better precision is obtained by the air-heated oven method. The time requiredfor drying ofcocoa beans is about 30 minutes by the proposed method as against 16 hours by the conventional technique.